The Interplay between S-Glutathionylation and Phosphorylation of Cardiac Troponin I and Myosin Binding Protein C in End-Stage Human Failing Hearts - Heidi Budde; Roua Hassoun; Melina Tangos; Saltanat Zhazykbayeva; Melissa Herwig; Marharyta Varatnitskaya; Marcel Sieme; Simin Delalat; Innas Sultana; Detmar Kolijn; Kamilla Gömöri; Muhammad Jarkas; et al. (MDPI AG, 2021)
Oxidative stress is defined as an imbalance between the antioxidant defense system and the production of reactive oxygen species (ROS). At low levels, ROS are involved in the regulation of redox signaling for cell protection. However, upon chronical increase in oxidative stress, cell damage occurs, due to protein, DNA and lipid oxidation. Here, we investigated the oxidative modifications of myofilament proteins, and their role in modulating cardiomyocyte function in end-stage human failing hearts. We found altered maximum Ca2+-activated tension and Ca2+ sensitivity of force production of skinned single cardiomyocytes in end-stage human failing hearts compared to non-failing hearts, which was corrected upon treatment with reduced glutathione enzyme. This was accompanied by the increased oxidation of troponin I and myosin binding protein C, and decreased levels of protein kinases A (PKA)- and C (PKC)-mediated phosphorylation of both proteins. The Ca2+ sensitivity and maximal tension correlated strongly with the myofilament oxidation levels, hypo-phosphorylation, and oxidative stress parameters that were measured in all the samples. Furthermore, we detected elevated titin-based myocardial stiffness in HF myocytes, which was reversed by PKA and reduced glutathione enzyme treatment. Finally, many oxidative stress and inflammation parameters were significantly elevated in failing hearts compared to non-failing hearts, and corrected upon treatment with the anti-oxidant GSH enzyme. Here, we provide evidence that the altered mechanical properties of failing human cardiomyocytes are partially due to phosphorylation, S-glutathionylation, and the interplay between the two post-translational modifications, which contribute to the development of heart failure.